Implementation of the Supervisory Function of Commission D of the Regional People's Representative Council on the Secondary Education Sector Budget - Asep Syaripudin; Achmad Sanusi; Daeng Arifin; Achmad Mudrikah (Tarbawi, 2021)
This study aims to describe and analyze the implementation of monitoring of budget realization in the secondary education sector by Commission D DPRD of Bandung City. This research uses descriptive qualitative research with analytical methods. The author acts as the main instrument in capturing data and information using observation, interview, and documentation study techniques, then analyzing the data in three stages: reduction, presentation, and verification. The results of the study found that the supervision of Commission D DPRD of Bandung City in monitoring the use of the secondary education budget still needs to be improved, there is a need for high commitment, there is a need for stable consistency, the need for transparency is in urgent need of coordination with related elements. Commission D DPRD of Bandung City in overseeing planning has implemented management principles, including involving various components involved in planning, although it needs improvement from the internal and external analysis. Commission D DPRD of Bandung City in carrying out supervision strives for continuity between planning and high implementation, although it is necessary to increase the professionalism of members of supervision in information technology. In conducting supervision, Commission D DPRD of Bandung City has transparently been by its duties, and reporting is well structured and easily accessible to the public, although it needs improvement from various aspects. Constraints in carrying out the budget oversight function are consistency and accountability and soft and hard skills. To overcome these obstacles, Commission D DPRD of Bandung City cooperates with various components, either directly or indirectly.